An Analysis of Conversational Implicature and Presuppositions Found in Nias Movie the “Iraono Sifagohi Tödö” - Opirman Waruwu (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study analyzes the types of conversational implicatures and categories of presupposition found in the Nias movie Iraono Sifagohi Tödö. Adopting a qualitative method, the research utilizes primary data derived from the film's dialogue transcriptions. The researcher employed reading, observation, and note-taking procedures to collect data, which were subsequently analyzed using a descriptive qualitative approach to interpret meanings and concepts. The results identified 20 instances of conversational implicature: 11 generalized and 9 particularized implicatures. Furthermore, the analysis revealed all six categories of presupposition: existential, factive, non-factive, lexical, structural, and counterfactual. Based on these findings, it can be concluded that research on conversational implicatures and presuppositions remains an underexplored topic. Therefore, the researcher encourages future studies to examine other linguistic aspects and objects. This analysis contributes to a deeper understanding of pragmatics within Nias cinema, highlighting how context shapes meaning and how underlying assumptions are structured in dialogue.